2015
DOI: 10.1007/s10935-015-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in a Community-Based Family Intervention: Replication of Two Coding Schemes

Abstract: Although program adaptation is a reality in community-based implementations of evidence-based programs, much of the discussion about adaptation remains theoretical. The primary aim of this study was to replicate two coding systems to examine adaptations in large-scale, community-based disseminations of the Strengthening Families Program for Parents and Youth 10-14, a family-based substance use prevention program. Our second aim was to explore intersections between various dimensions of facilitator-reported ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…This supports past qualitative findings that community therapists frequently tailor the terminology or language used to meet the needs of their clients and improve client engagement (Gibbs, Krieger, Cutbush, Clinton-Sherrod, & Miller, 2016; Stirman et al, 2013). However, in past studies of community implementation of EBPs, therapists also commonly reported omitting core components from practices or making other adaptations that might represent drift from fidelity (Cooper, Shrestha, Hyman, & Hill, 2015; Stirman et al, 2013; Stirman et al, 2015). Whether such adaptations have an impact on clinical outcomes is an important question for further study.…”
Section: Discussionmentioning
confidence: 99%
“…This supports past qualitative findings that community therapists frequently tailor the terminology or language used to meet the needs of their clients and improve client engagement (Gibbs, Krieger, Cutbush, Clinton-Sherrod, & Miller, 2016; Stirman et al, 2013). However, in past studies of community implementation of EBPs, therapists also commonly reported omitting core components from practices or making other adaptations that might represent drift from fidelity (Cooper, Shrestha, Hyman, & Hill, 2015; Stirman et al, 2013; Stirman et al, 2015). Whether such adaptations have an impact on clinical outcomes is an important question for further study.…”
Section: Discussionmentioning
confidence: 99%
“…There are increased efforts to implement evidence‐based interventions (EBIs) in routine mental health services. Within these efforts, there is a strong emphasis on delivering EBIs with fidelity to reproduce effective intervention outcomes; however, the need to maintain intervention integrity must be balanced with the need to adapt interventions to respond to local settings and client preferences to increase intervention sustainment (August, Gewirtz, & Realmuto, ; Cooper, Shrestha, Hyman, & Hill, ). Indeed, a number of key implementation outcomes (Proctor et al, ) are important to understanding and informing adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of EBIs in mental health settings indicates that therapists utilize a high rate of adaptations when implementing interventions (Aarons et al, ; Cooper et al, ; Lau et al, ; Stirman, Miller, Toder, & Calloway, ). Stirman et al () argued that classifying adaptations is crucial for accurate measurement of the impact of different types of adaptations on clinical (e.g., effectiveness) and implementation (e.g., engagement and sustainment) outcomes and initially classified adaptations as fidelity‐consistent (adaptations that do not change the core elements of the EBI) versus fidelity‐inconsistent (adaptations that change core EBI components; Stirman et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from other areas show that adaptation is the rule rather than the exception [18]. An accumulation of findings has shown that between 44 and 88% of users adapt the procedure, dosage, content, format, and/or target group when using EBIs (e.g., [19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%